Cripples' Training College (London and District) : Bernhard Baron Memorial (leaflet) (1936)
1936 1936 1930s 4 pages : illustrations Cripples' Training College (LONDON & DISTRICT) BERNHARD BARON MEMORIAL [photograph] Leatherhead Court, Surrey. [photographs] Crippled Trainees in workshop and in greenhouse. Donations, large or small, will be most gratefully received and should be sent to the Hon. Treasurer, The Lord Moynihan, Cripples' Training College (Office) 27, Marsham Street, Westminster, S.W.1. 292/841.51/2/22